Keap1 mutation renders lung adenocarcinomas dependent on Slc33a1 - Romero, Rodrigo; Sánchez-Rivera, Francisco J; Westcott, Peter M K; Mercer, Kim L; Bhutkar, Arjun; Muir, Alexander; González Robles, Tania J; Lamboy Rodríguez, Swanny; Liao, Laura Z; Ng, Sheng Rong; Li, Leanne; Colón, Caterina I; et al. (Nature cancer, 2020)
Approximately 20-30% of human lung adenocarcinomas (LUAD) harbor loss-of-function (LOF) mutations in Kelch-like ECH Associated-Protein 1 ( ), which lead to hyperactivation of the nuclear factor, erythroid 2-like 2 (NRF2) antioxidant pathway and correlate with poor prognosis . We previously showed that mutation accelerates KRAS-driven LUAD and produces a marked dependency on glutaminolysis . To extend the investigation of genetic dependencies in the context of mutation, we performed a druggable genome CRISPR-Cas9 screen in -mutant cells. This analysis uncovered a profound mutant-specific dependency on solute carrier family 33 member 1 ( ), an endomembrane-associated protein with roles in autophagy regulation , as well as a series of functionally-related genes implicated in the unfolded protein response. Targeted genetic and biochemical experiments using mouse and human -mutant tumor lines, as well as preclinical genetically-engineered mouse models (GEMMs) of LUAD, validate as a robust -mutant-specific dependency. Furthermore, unbiased genome-wide CRISPR screening identified additional genes related to dependency. Overall, our study provides a strong rationale for stratification of patients harboring -mutant or NRF2-hyperactivated tumors as likely responders to targeted SLC33A1 inhibition and underscores the value of integrating functional genetic approaches with GEMMs to identify and validate genotype-specific therapeutic targets.